Removal of cobalt from lubricant oil by the use of bentonite: equilibrium, kinetic and adsorption preliminary studies - VALERIA CUCCIA; SANDRO ROGÉRIO NOVAES SELES; ANA CLAUDIA QUEIROZ LADEIRA (Brazilian Journal of Radiation Sciences)
Radionuclides may contaminate lubricant oils in nuclear power plants. In Brazil, this kind of waste has been stored in the generator’s facilities, awaiting treatment alternatives. This work intends to investigate a process to treat it for final deposition, using bentonite as sorbent material. This process will result in decontaminated oil, free from radiological control, and radioactive loaded sorbent, with considerable volume reduction of the radioactive waste. The study focuses in cobalt removal from a simulated oil waste (non-active). The production of the simulated waste is described. Bentonite was used for equilibrium time determination, kinetic and adsorption studies. Cobalt adsorption equilibrium was rapidly attained after 30 minutes. The data was used for modelling the system’s kinetic, applying the pseudo first and pseudo second order equation models. Experimental data fitted to pseudo second order model, supporting the assumption that the adsorption is due to chemisorption. Batch sorption tests were conducted and the results fitted to Langmuir and Freundlich sorption models. Both isotherm models chosen for this work did not fit to the experimental data. Thus, these are preliminary results and the studies must be repeated to evaluate data variability and better statistical inference. Other isotherm models must be evaluated to choose the best fitted one and describe the sorption of cobalt on bentonite in oil matrix. Even though, bentonite has considerable potential as sorbent for the removal of cobalt from lubricant oil. Finally, the results might be extended to other kinds of radioactive oils and radioactive organic wastes.